Usability of the GAIMplank Video Game Controller for People With Mobility Impairments: Observational Study - Laurie A Malone; Christen J Mendonca; Sangeetha Mohanraj; Samuel R Misko; Joseph Moore; James Michael Brascome; Mohanraj Thirumalai (JMIR Publications, 2023)
BackgroundReplacing sedentary behaviors during leisure time with active video gaming has been shown to be an enjoyable option for increasing physical activity. However, most off-the-shelf active video gaming controllers are not accessible or usable for individuals with mobility impairments. To address this requirement, a universal video game controller (called the GAIMplank) was designed and developed. ObjectiveThis study aimed to assess the usability of the GAIMplank video game controller for playing PC video games among individuals with mobility impairments. Measures of enjoyment, perceived exertion, and qualitative data on the user experience were also examined. MethodsAdults (aged 18-75 years) with a mobility impairment were recruited to participate in a single testing session in the laboratory. Before testing began, basic demographic information, along with minutes of weekday and weekend physical activity, minutes of weekday and weekend video game play, and video game play experience were collected. The GAIMplank was mapped to operate as a typical joystick controller. Depending on their comfort and functional ability, participants chose to play seated in a chair, standing, or in their own manual wheelchair. Leaning movements of the trunk created corresponding action in the game (ie, lean right to move right). The participants played a total of 5 preselected video games for approximately 5 minutes each. Data were collected to assess the usability of the GAIMplank, along with self-efficacy regarding execution of game play actions, rating of perceived exertion and enjoyment for each game, and overall qualitative feedback. ResultsA total of 21 adults (n=15, 71% men; n=6, 29% women) completed the usability testing, with a mean age of 48.8 (SD 13.8; range 21-73) years. Overall, 38% (8/21) of adults played while standing, 33% (7/21) of adults played while seated in a chair, and 29% (6/21) played in their own manual wheelchair. Scores from the System Usability Scale indicated above average (74.8, SD 14.5) usability, with scores best for those who played seated in a chair, followed by those standing, and then individuals who played seated in their own wheelchairs. Inconsistencies in the responsiveness of the controller and general feedback for minor improvements were documented. Rating of perceived exertion scores ranged from light to moderate intensity, with the highest scores for those who played seated in a chair. Participants rated their experience with playing each game from above average to very enjoyable. ConclusionsThe GAIMplank video game controller was found to be usable and accessible, providing an enjoyable option for light-to-moderate intensity exercise among adults with mobility impairments. Minor issues with inconsistencies in controller responsiveness were also recorded. Following further development and refinement, the next phase will include a pilot exercise intervention using the GAIMplank system.